1968
DOI: 10.1029/ja073i011p03459
|View full text |Cite
|
Sign up to set email alerts
|

Universal-time control of the low-energy electron fluxes in the polar regions

Abstract: Particle observations by the Rice University/ONR satellite Aurora 1 have revealed a large universal‐time variation in the low‐energy electron fluxes in the northern polar region during summertime. The electron fluxes are highest near 1800–2000 UT, both on the night‐ and the day‐side of the earth above ∼75° invariant latitudes, whereas a minimum in the fluxes is reached between 0600 and 1200 UT. It is suggested that these variations are associated with the diurnal changes in the tilt of the geomagnetic axis rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1969
1969
1998
1998

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Another suggested explanation is based on soft electron precipitation [Duncan, 1962[Duncan, , 1969Pike, 1970], which could vary with universal time. Such a fluctuation in the high-latitude limit of precipitation has been reported by Maehlum [1968] for the north polar region with a maximum at 1800-2000 UT. The suggested explanation for this latter phenomenon is the daily change in orientation of the magnetic poles with respect to the earth-sun line.…”
supporting
confidence: 69%
“…Another suggested explanation is based on soft electron precipitation [Duncan, 1962[Duncan, , 1969Pike, 1970], which could vary with universal time. Such a fluctuation in the high-latitude limit of precipitation has been reported by Maehlum [1968] for the north polar region with a maximum at 1800-2000 UT. The suggested explanation for this latter phenomenon is the daily change in orientation of the magnetic poles with respect to the earth-sun line.…”
supporting
confidence: 69%
“…They suggested that the UT eect is more fundamental and re¯ects an interaction between interplanetary magnetic ®eld orientation and the Earth's magnetic dipole inclination. A similar suggestion, regarding UT eects in auroral particle precipitation, was given by Maehlum (1968) who pointed out there are large UT variations during the day in the angle between the Earth's magnetic axis and the Sun-Earth line. The change in the orientation of the Earth's ®eld relative to the direction of the solar wind can cause`wagging' in the Earth's magnetotail and thus aect the longitudinal distribution of the particle precipitation.…”
Section: Conclusion and Discussionmentioning
confidence: 80%
“…An early study of the longitudinal dependence in auroral particle precipitation was conducted by Loughnan (1961) who suggested that there is a marked longitudinal leakage of auroral particles from the trapped-radiation regions. An experimental particle observation project from a satellite has revealed a large universal-time variation in low-energy electron¯uxes (Maehlum, 1968). He associated these variations with the diurnal changes in the tilt of the Earth's geomagnetic axis relative to the solar wind direction.…”
Section: Introductionmentioning
confidence: 99%
“…This region has been described as a 'soft' zone (Burch, 1968) or 'burst' zone (Hoffman, 1969). One of the important effects of the incidence of these low energy electrons on the earth's upper atmosphere is the production of ionization at F region levels and above (Maehlum, 1968;Burch, 1969; and Rees, 1969). The high latitude termination of the flux near the magnetic pole appeased to be responsible for the low 0 level of F region ionization and also of 6300 A intensity (Maehlum, 1969;Eather, 1969).…”
mentioning
confidence: 99%